The Relevance of Autoantigen Source and Cutoff Definition in Antichromatin (Nucleosome) Antibody Immunoassays - VILLALTA, DANILO; TOZZOLI, RENATO; BIZZARO, NICOLA; TONUTTI, ELIO; GHIRARDELLO, ANNA; DORIA, ANDREA (Annals of the New York Academy of Sciences, 2005)
: In the last few years, several reports have shown that chromatin (nucleosome) represents the main autoantigen‐immunogen in systemic lupus erythematosus (SLE) and that specific antibodies are an important marker of the disease. To verify the clinical sensitivity and specificity of antinucleosome autoantibodies (ANuAs), we evaluated three ELISA immunoassay methods using different autoantigen preparations: Quanta Lite Chromatin, Medizym Anti‐nucleo, and Nucleosome IgG Elisa. We compared the results with those obtained using two ELISA assays for determining anti‐native DNA (anti‐nDNA) antibodies: Axis‐Shield and EliA dsDNA. We tested sera from 321 patients: 101 with SLE and 220 controls—48 with infectious diseases; 73 with autoimmune rheumatic disease (20 with rheumatoid arthritis, 30 with systemic sclerosis, and 23 with primary Sjögren's syndrome), and 99 healthy subjects. Using the manufacturer‐recommended cutoff, the sensitivity for the three kits was 69%, 78%, and 74%, and specificity was 100%, 94.6%, and 95.0%, respectively. Using the cutoff corresponding to 95% specificity, the sensitivity of the methods for the ANuA assay was 86%, 77%, and 74%—higher than obtained with the two ELISA methods for anti‐nDNA (65% and 64%). This study demonstrates that (1) the commercial reagents employed in clinical laboratories for ANuA detection show good sensitivity and high specificity; (2) ANuAs are more sensitive than anti‐nDNA antibodies for diagnosing SLE; and (3) different solid‐phase antigen preparations and methods used to define cutoff levels may affect a test's clinical performance.